Performance Analysis of Window Type Air Conditioning with Addition of Heat Exchanger Equipment - Wirawan, I Ketut Gede (Jurnal Energi Dan Manufaktur; Vol 3, No.2 Oktober 2009, 2012)
One manner to be used to increase refregration effect is by flowing hot refrigerant out from condensor, it is then touched with the refrigerant out from evaporator on a heat exchanger of counterflow type. Experiment was done by taking samples of pressure at suction (p1) and discharge (p2) of compressor and box temperature (Tr1, Tr2, Tr3, Tr4). By knowing of pressure at suction (p1), the enthalpy into compressor is known. By assuming the process is isentropic (compressor), isobar (condenser and evaporator), and isenthalpy (expansion valve), the enthalpy into condensor, expansion valve and evaporator were known. In 60 minutes, compression work of air conditioning with heat exchanger is 31,588 kJ/kg, and without heat exchanger is 33,796 kJ/kg. Effect refrigeration average with modification is 155,55 kJ/kg and without modification was 153,40 kJ/kg so that coefficient of performance with modification more than without modification. Air conditioning with modification had initial refrigration rate was 67,193 J/s and 0,043 J/s at the end minute, meanwhile, refrigeration without modification had cooling rate at start 66,538 J/s and 0,935 J/s at the end.
Keywords: Compression work, Refrigeration effect, Coefficient of performance, Cooling rate